Initiating a Good Governance Formulation Model with a Perspective on Mainstreaming Poverty in Regional Budgeting - Angin, Ria; Emy Kholifah R.; Edhi Siswanto (Universitas Muhammadiyah Jember Press, 2023)
The target of increasing HDI which has become a priority for the regional government of Jember Regency requires a special strategy to achieve it, (1) The existence of regulations that enable the aspirations and interests of the poor to be accommodated; (2) There are clear benchmarks regarding achievement indicator targets for each SKPD program; (3) There is an agreement between the DPRD and the Regional Government regarding the percentage or ceiling of funds that must be provided for poverty alleviation programs.